Atlantoaxial Rotatory Subluxation: A Review for the Pediatric Emergency Physician. Issue 10 (October 2016) - Kinon, Merritt D.; Nasser, Rani; Nakhla, Jonathan; Desai, Rupen; Moreno, Jessica R.; Yassari, Reza; Bagley, Carlos A.
Abstract : Abstract: Pediatric emergency physicians must have a high clinical suspicion for atlantoaxial rotatory subluxation (AARS), particularly when a child presents with neck pain and an abnormal head posture without the ability to return to a neutral position. As shown in the neurosurgical literature, timely diagnosis and swift initiation of treatment have a greater chance of treatment success for the patient. However, timely treatment is complicated because torticollis can result from a variety of maladies, including: congenital abnormalities involving the C1-C2 joint or the surrounding supporting muscles and ligaments, central nervous system abnormalities, obstetric palsies from brachial plexus injuries, clavicle fractures, head and neck surgery, and infection. The treating pediatrician must discern the etiology of the underlying problem to determine both timing and treatment paradigms, which vary widely between these illnesses. We present a comprehensive review of AARS that is intended for pediatric emergency physicians. Management of AARS can vary widely bases on factors, such as duration of symptoms, as well as the patient's history. The goal of this review is to streamline the management paradigms and provide an inclusive review for pediatric emergency first responders.